Risk Management In Hospital Filing Unit - Sri Wahyuningsih Nugraheni; Erma Nurhayati Firdaus; Valentina Dita Agustine (Proceeding of International Conference on Science, Health, And Technology, 2019)
The risk in the filing unit is influenced by five factors namely physical factors, chemical factors, biological factors, physiological factors, and production process factors. There are two risk management actions, namely to prevent and improve. Risk management is carried out with the aim of preventing work accidents and decreasing work productivity in hospital filing unit. The aim of this study was to identifying risks, controlling risks, reporting risks, monitoring risks and attitudes to risks in the filing unit. This research is a descriptive study with cross sectional approach. Research subjects were manajer of the medical record, manajer of the registration room, and the filing officer. While the object of research is the Rumah Sakit Islam Klaten filing unit. The research instruments were observation and interview guidelines. Data processing by collecting, editing, tabulating and presenting data. Analysis data is descriptively. Rumah Sakit Islam Klaten has identified risks and found several risk factors, namely physical factors, chemical factors, biological factors, physiological factors and production process factors. Risk control has also been carried out based on the type of risk that occurs. As for risk management reporting, it has never been done so evidence of reporting is not available. Risk management monitoring has never been done. Rumah Sakit Islam Klaten has determined its attitude based on risk factors namely stopping or avoiding risk and reducing risk. Rumah Sakit Islam Klaten should report the risks so that risks can be recorded and the existence of appropriate control measures and risk management monitoring so that any risks that occur can be monitored and known the development of these risks.